2020
DOI: 10.1038/s41467-020-20207-y
|View full text |Cite
|
Sign up to set email alerts
|

MaTAR25 lncRNA regulates the Tensin1 gene to impact breast cancer progression

Abstract: Misregulation of long non-coding RNA (lncRNA) genes has been linked to a wide variety of cancer types. Here we report on Mammary Tumor Associated RNA 25 (MaTAR25), a nuclear enriched and chromatin associated lncRNA that plays a role in mammary tumor cell proliferation, migration, and invasion, both in vitro and in vivo. MaTAR25 functions by interacting with purine rich element binding protein B (PURB), and associating with a major downstream target gene Tensin1 (Tns1) to regulate its expression in trans. The T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 83 publications
1
59
0
Order By: Relevance
“…Xiao et al (2020) found that the lncRNA MAFG-AS1, which is highly expressed in bladder urothelial carcinoma, is correlated with aggressive characteristics and poor prognosis of bladder urothelial carcinoma. As for BRCA, IRNAS HOTAIR, SPRY4-IT1, GAS5, MATAR25, PANDAR, and MATAR25, new players in tumor development and prognosis, have shown owning potential clinical applications in BRCA (Soudyab et al, 2016;Nagini, 2017;Chang et al, 2020). In addition, viable ways have been considered to predict the potential BRCA lncRNAs by performing highthroughput data based on bioinformatics methods (Guo et al, 2018;Chi et al, 2019;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al (2020) found that the lncRNA MAFG-AS1, which is highly expressed in bladder urothelial carcinoma, is correlated with aggressive characteristics and poor prognosis of bladder urothelial carcinoma. As for BRCA, IRNAS HOTAIR, SPRY4-IT1, GAS5, MATAR25, PANDAR, and MATAR25, new players in tumor development and prognosis, have shown owning potential clinical applications in BRCA (Soudyab et al, 2016;Nagini, 2017;Chang et al, 2020). In addition, viable ways have been considered to predict the potential BRCA lncRNAs by performing highthroughput data based on bioinformatics methods (Guo et al, 2018;Chi et al, 2019;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that lncRNAs acted as a key regulator in the pathogenesis, progression, and phenotype development of breast cancer (32). Growing data delineated LncRNAs dysregulated in breast cancer (33)(34)(35)(36)(37). As previously described, lncRNA FGD5-AS1 participated as an essential mediator in various cancer.…”
Section: Discussionmentioning
confidence: 71%
“…Considering this special edition focused on the roles of protein tyrosine phosphatases in signaling, with an emphasis on therapeutic strategies, the pseudophosphatases' signaling mechanisms linked to diseases, myotubularins, tensins, and STYX pseudophosphatases, was discussed in more detail. [68] The proteins here all contain alterations in their catalytic active site motifs that are associated with loss of phosphatase function.…”
Section: Pseudophosphatases In Diseasesmentioning
confidence: 99%
“…Since tensin 1 and tensin 2 are pseudophosphatases, they will be described in more detail. Knockout mouse studies have linked their functionality to muscle regeneration and to diseases (Figure 4) such as kidney failure, cancer, chronic obstructive pulmonary disease (COPD), etc., [31,64,66,68,94,95]. Tensin 1 is a 220-kD cytoplasmic phosphoprotein localized to focal adhesions, serving as a molecular bridge linking the extracellular matrix (ECM), actin cytoskeleton, and signal transduction [64,66,95,96].…”
Section: Tensin In Diseasementioning
confidence: 99%
See 1 more Smart Citation